Análisis de la inversión extranjera directa (IED) y el crecimiento económico para 9 países latinos, agrupados por su nivel de ingreso, utilizando técnicas de datos panel, periodo 1978-2018 - Herrera Herrera, María Esperanza (2022)
Foreign Direct Investment has become the main determinant variable of economic growth, globally, regionally and nationally, especially in Latin America; therefore, this research seeks to evaluate the incidence of FDI in economic growth, for 9 Latin countries grouped by income level during 1978-2018, through an econometric analysis with panel data techniques. GDP was used as the dependent variable and FDI as the independent variable, and to extend the analysis, control variables were included to improve the economic study. The data were estimated from the official World Bank website (2022). Panel data techniques were used, with a Generalized Least Squares (GLS) model. The main results are reflected in the positive and significant incidence of Foreign Direct Investment in Gross Domestic Product, in the PIA and PIMA and a negative relationship in the PIMB. It is concluded that the effects of FDI on economic growth are positive and significant, with more efficiency in the PIA and each one of the variables, including the control variables, are efficient in the long run. As a result of this work, it is suggested that policies should focus on attracting and encouraging foreign investment to reach each economy, with clear, effective and efficient rules, where human capital is capable and disinterested, in a decent work environment, which is durable, broad and open to foreign trade and therefore to the economic development of each country.